High Peaks - Whitney, C. V. (Cornelius Vanderbilt), 1899-1992 (Book collections on Project MUSE., 1977)
Rarely is one allowed such an intimate glimpse into the ""high peaks"" of a life so extraordinary and exciting as that of C.V. Whitney. Scion of a distinguished family of great wealth, ""Sonny"" Whitney early displayed the zest for life and the adventurous spirit which have led him into a varied array of achievements remarkable even for the Whitney clan. A pilot in World War I and an AAF officer in World War II who was involved in such events as Iwo Jima and El Alamein, Whitney later, as assistant secretary of the air force, played a crucial role in ending the Berlin blockade. A sportsman with.